Cancel Culture, Commodification Message, and Middle East War: Impact on Multinational Corporations in Indonesia - Ramadhani, Amelia; Utari, Prahastiwi; Hastjarjo, Sri (Journal of Social Interactions and Humanities, 2024)
The ongoing conflict between the Palestinians and Israelis has prompted a range of attitudes among the countries with which they have relations. The emergence of the cancel culture phenomenon, a movement to boycott certain companies' products, has raised growing concerns. The paper analyzes the social media messages of multinational corporations regarding products that are boycotted by consumers who see them as haram and pro-American because of their alliance with Israel. Through an analysis of digital media content from several multinational companies related to Israeli attacks on Palestine and the issuance of MUI Fatwa No. 83/2023, two frames of controlled media content emerge.